Comparative Analysis of Dual-System Curriculum in ELT: The Merdeka Curriculum VS The Pesantren Curriculum - Bistomy, Zaky El; Perdana, Purnama Rika; Hillalliyati, Nazmi (Merwinspy Publisher, 2025)
This study examines the comparative implementation of the Dual-System Curriculum to accommodate government’s standard requirement. The Dual-System curriculum that is mentioned here is the Merdeka Curriculum and the Islamic boarding school (Pesantren) curriculum in the context of English Language Teaching (ELT), seen by comparing the content of textbooks used. The focuses of this research consist of (1) the challenges and strategies in delivering lessons from both distinct textbooks, and (2) the differences between the textbooks (the content). This research employs a qualitative method by comparing both curricula, analyzing the implementation through observation and interviews, and presenting the data chronologically based on the aims of this research. Findings highlight two major things: (1) challenges identified include resource limitations, teacher training needs, and varying student proficiency levels, while the strategies used by the teacher is by applying blended strategies (incorporating communicative activities) within the framework of the pesantren curriculum and structuring grammar-focused lessons within the Merdeka curriculum. Finally, this research contributes to the discourse on curriculum design and its role in shaping effective language education in diverse educational contexts.